PENGARUH PSIKOEDUKASI TERHADAP PENURUNAN TINGKAT POSTPARTUM BLUES: LITERATURE REVIEW - Ariani Fatmawati; Rizki Julia Wahyuni; Bhekti Imansari (Jurnal Ilmu Keperawatan dan Kebidanan, 2022)
This research is overwhelmed by the high number postpartum depression or postpartum blues than years in, so that care for postpartum depression and also the postpartum blues needed. A series of duty and adding a role in mother postpartum can cause for stress. The impact of negative experienced by mother in the short term activity which is depply disturbed. Psychoeducation is intervention can be given at mother with postpartum depression in lowering the level of stress. This study aims to identify the influence of the decrease in the level intervention psychoeducation postpartum blues. The research design used a literature review with an Evidence Based Nursing (EBN) approach from 10 relevant research articles. Search for research articles from several database, namely ProQuest, PubMed, Goggle Scholar and Research Gate. The criteria for inclusion in the study of literature is pregnant women, postpartum mother, patients postpartum blues and mother who suffered from postpartum depression, use psychoeducation intervention, with a design researvh pre-quasy experimental, quasy-experimental and randomized controller trial, in vulnerable time 2016-2021 properly published articles, and use Indonesian or English. The result of this research explained that psychoeducation can be given in 2 session with duration 30-45 minutes late. Instrument EPDS (Edinburgh Postnatal Depression Scale) a device used to measure the depression that serve as a measuring instrument in knowing the success of therapy. The result of a study literature showing that psychoeducation effect on the postpartum blues. This study literature could be to improvement quality of competence nurse in the servise of martenity be able to provode psychoeducation on the postpartum.